Processo de criação de produtos de comunicação e marketing para negócios de impacto: estudo de caso da Colaboradora Social - Souza, Rodrigo Biajoni de (2021)
The nonprofit organizations and social impact businesses face many challenges to implement their projects and process on an ongoing basis. Communication and marketing are crucial areas to its positioning and to reach the expected goals in many areas, including fundraising, attraction of volunteers, sales, promoting of actions, among others. Looking forward to contribute to nonprofit and social businesses entrepreneurs, this research developed a new business model for Colaboradora, an initiative capable of promoting capacity building services in the area of marketing and communication, through the Stage-Gate methodology, which organizes the structuring of new processes through five development stages and evaluation gates, besides tools from Design Thinking and examples such as SWOT Analysis, Business Model Canvas, Minimum Viable Product (MVP), Empathy Map and Theory of Change. Beginning with a bibliographic review that covers the roots of the Sector 2.5 and Third Sector development around the world and in Brazil, up to the usage of an exploratory research with social entrepreneurs from Rio de Janeiro, this document sought to present the main characteristics, needs and offers of this public considering the communication and marketing fields. The territorial context and the currently existing offer directly impacts in the valuation and perception that social entrepreneurs demonstrate in face of communication and marketing for their activities. The research implements a pilot that works directly with the target audience, through the launch of an ebook and an online course, directly impacting over 200 social organizations, as well as developed an action plan for Colaboradora’s development in a 6 months period.